E-Government Service Evaluation of Batu City Health Dept.using e-Govqual Approach and IPA Analysis - Evi Wahyuni EDW; Dharma Pradana; Yasina Karina (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
E-Government is an application of government information system technology to support public service system and dissemination of information from government to society that used in every element of government. Batu City Health Office website (http://dinkes.batukota.go.id) is part of Batu City Government e-Government system that was built to support publication of government information to the public. According to observations, there was a decline in visitors from the number 150 visitors in October 2017 to 50 visitors in November 2017. While in December 2017 stable at the number 50 visitors. Based on the anomaly incident, there needs to be an evaluation of e-Government in Batu City Health Office by doing the assessment of website service quality from the user side. This evaluation uses e-Govqual and Heuristic Evaluation methods. Assessment of e-govqual attributes on performance values and interests in the IPA quadrant resulted in the conclusion that there are 24 attributes in A and C quadrants in the IPA quadrant that need to improve attribute quality. Suggestions based on quadrant A and C in the form of recommendation improvement in the form of recommendation mockup based on 10 principles of heuristic evaluation